Think globally and act locally: assessing the environmental impacts of the Nigerian threatened native trees project - Awoyemi, A.G.; Olasupo, O.E.; Ajayi, A.D.; Bown, D. (Elsevier, 2024)
The environmental and socio-economic impacts of the Nigerian Threatened Native Trees Project are presented. This project conducted propagation trials and developed a freely downloadable online Manual of Tree Propagation (MTP) for 55 native tree species, training 146 local experts (32 women and 114 men) during the period (November 2015—December 2022). We used Google Analytics and interviews to assess the impacts of this project from January 2018—July 2023 (iEcology). Results show that the MTP has been downloaded 1013 times, with the star apple Gambeya albida (76), gum tree Tetrapleura tetraptera (65) and bitter kola Garcinia kola (50) topping the list. These downloads were from 15 countries spread across the world. Interestingly, the seven African countries that downloaded the MTP are concentrated in the tropical belt with similar floristic composition. The native range of almost all the propagated species overlaps with these African countries, suggesting the adoption of our MTP, and practically demonstrating the conservation mantra of “think globally, act locally”. In addition, the MTP has been deployed for academic work (i.e., grey literature) and reforestation (e.g., covering c. 1200 ha in Nigeria). By revealing suitable propagation techniques and training local foresters, our approach could boost the utilization of native tree species for reforestation in Africa.